Implementation of E-government in the Public Service Sector as a Strategy for Preventing Blue-Collar Crime - Susaningsih, Catur; Gibran, Atsil Syah; Ardiansyah, Andika (Journal of Administration and International Development, 2024)
Abstract. The implementation of e-government has become a strategic step in enhancing efficiency and transparency in public services, and it holds potential for reducing blue-collar crimes such as corruption and embezzlement. This study analyzes the application of e-government in Indonesia, with a particular focus on its role in preventing blue-collar crime within the public service sector. Using a qualitative approach and case study methodology, the research identifies factors influencing the effectiveness of e-government in crime prevention. The findings indicate that, while e-government has significant potential to improve the quality of public services, its success is heavily dependent on factors such as technological infrastructure, human resource competencies, and supportive policies and regulations. This research contributes valuable insights into the role of e-government in preventing blue-collar crime and offers recommendations for enhancing e-government implementation in Indonesia.